PEMISAHAN SUSU KEDELAI DENGAN CARA SENTRIFUGASI - Freddy Riando H Nasution; R. Mursidi Mursidi; Haisen Hower (Universitas Sriwijaya, 2012)
The purpose of this research was to study the effect of centrifugation method in soy milk separation. The research was conducted in the Laboratory of Agricultural Workshop, Department of Agriculture, Faculty of Agriculture Sriwijaya University Indralaya, from January to July 2012. This research was consisted of six levels of centrifugation duration (30, 60, 90, 120, 150 and 180 s) with three replications. Parameters observed were yield, capacity, and separation rate. The result showed that the separation process was completely finished at 60th second of centrifugation time. The average of separation rate was 110 g/s for the 30th second and 82.2 g/s for the 60th second of centrifugation time, with the yield of 83.3%.Keywords: Separation, Soymilk, Centrifugation